Determinants Of Sustainable Operations Excellence: The Mediating Effects Of Supply Chain Integration And Digital Technology Adoption - Ahmad Zainal Abidin bin Abd Razak (Tanjung Malim, 2024)
Determinants Of Sustainable Operations Excellence: The Mediating Effects Of Supply Chain Integration And Digital Technology Adoption by Ahmad Zainal Abidin bin Abd Razak